The stands of Copernicia tectorum (Arecaceae) in the Caribbean lowlands of Colombia: a managed pioneer palm facing river dynamics - Torres, Claudia (2015)
Copernicia tectorum is a palm that grows in large populations on seasonally flooded savannas in the Caribbean region of Colombia, where its stems and expanded leaves are used in construction, and its unexpanded leaves are used to make handicrafts. We studied abundance and population structure in 34 plots of 20×10m (0.68 ha) of three localities (Plato, Córdoba and Magangué) at the Mompox Depression, an inner delta formed by the confluence of four large rivers. We recorded growth and mortality of 164 palms of different size classes over 13 months, and additionally we estimated seedling and juvenile mortality in two 10x10m plots within the same sites. Data analysis using Kolgomorov-Smirnov (KS), Kruskal-Wallis and Mann-Whitney tests were made on Statgraphics Plus and SPSS. We related the structure and dynamics of the palm stands to flood intensity. Copernicia tectorum has the fastest leaf production rate recorded for any palm (19-23 leaves/year in subadults and adults), and a short life span of ca. 46 years. The abundance, density and high leaf production rate of this palm offers a great potential for the sustainable use of its unexpanded leaves (especially at Plato, where there are ca. 480ha of palm stands with 300-1 000 individuals/ha), as leaf harvest from subadult and adult individuals does not appear to affect population structure. The palm is a pioneer of the flood plain, and the palm stands at particular sites appear to wax and wane following sedimentation dynamics, in which the species plays in important role. Current population structure and the scarce recruitment of juveniles at the study site suggest that the population is waning in that site. Management actions should be taken to reestablish natural river dynamics at the lagoon complex where the palm grows. Appropriate management of palm stands may contribute to minimize any negative effects of river dynamics.